Visual portrait of the main character in “Landscape and genre” by N. S. Leskov A Winter’s Day - Lemishka, Anna Tarasovna (Известия Саратовского университета. Новая серия. Серия Филология: Журналистика, 2023)
The problem of the interaction of words and images in the works of N.S. Leskov is currently the least studied. The genre subtitle of the late story A Winter’s Day (1894) – “Landscape and genre” encourages us to consider the work in the aspect of the designated problem. O. V. Evdokimova (1980), B. S. Dykhanova (2013), O. V. Chervinskaya (2018), D. S. Rivanenkova (2021) analyze the features of the genre, taking into account the meanings of the subtitle. The specific nature of the genre of the work determines the poetics of the portrait in it, which has not been studied before. The portrait of the main character in the story by N.S. Leskov is interpreted as a visual portrait, a visual image. The understanding of the “visual image” is based on literary, cultural and art criticism works of the modern scientists. The climax in the poetics of the portrait of the main character, Lydia, is a comparison with the goddess Diana. The analysis of sculptural and pictorial contexts (“Goddess Artemis with a deer” Tanagra, end of 4th century B.C., “Diana of Versailles”, circa 325 B. C., “Diana Resting”, 1732–1733, “The Hunt of Diana”, 1616–1620 etc.) illustrates that the writer shows the world through the lens of the depicted. Contextual connections of Lydia’s portrait with the image of Diana actualize the visual image in the work of N. S. Leskov. The main character of the story is an exceptional character against the background of other (everyday) characters of the work, since her visual portrait, which includes the features of pictorial and sculptural images, was created as a separate work of art. The article shows that the poetics of a visual portrait is determined by diﬀerent facets of the genre – “Landscape and genre”: the everyday and the existential ones.